Global Random Walk simulations for sensitivity and uncertainty analysis of passive transport models - Suciu, Nicolae; Vamo̧s, Cǎlin; Vereecken, Harry; Knabner, Peter (Mathematics and its Applications : Annals of the Academy of Romanian Scientists, 2011)
The Global Random Walk algorithm (GRW) performs a simultaneous tracking on a fixed grid of huge numbers of particles at costs comparable to those of a single-trajectory simulation by the traditional Particle Tracking (PT) approach. Statistical ensembles of GRW simulations of a typical advection-dispersion process in groundwater systems with randomly distributed spatial parameters are used to obtain reliable estimations of the input parameters for the upscaled transport model and of their correlations, input-output correlations, as well as full probability distributions of the input and output parameter
Keywords: Groundwater contamination; Monte carlo methods; Probabilistic particle methods; Transport processes